Pendidikan Karakter Siswa Melalui Hidden Curriculum Di Madrasah Ibtidaiyah (Mi) Tarbiyatul Aulad Nglanjuk Cepu Blora Jawa Tengah Tahun 2015 - Al Amin, Moh (2016)
Character can be defined how to apply or carve the value of kindness in the form of action or behavior, so people who are dishonest, cruel, greedy, and behave ugly people say ugly character. Conversely, people whose behavior is in accordance with the moral code called a noble character. In growing character education, the need for awareness of the various parties to initiate and become habituation. Education play a strong role in shaping the character of a society. Islamic Elementary School (MI) Tarbiyatul Aulad Nglanjuk Blora Cepu, Central Java as the delivery of educational institutions based on religion should familiarize character education in any learning activities and behavior of educators and students in the school environment. On the basis of the author conducted research into how the embedded character education through the hidden curriculum in Islamic Elementary School (MI) Tarbiyatul Aulad Nglanjuk Cepu Blora. The problems of this study there are two, namely: a. Is the foundation of character education at Government Elementary School (MI) Tarbiyatul Aulad Nglanjuk Cepu Blora? and b. How does character education at Government Elementary School (MI) Tarbiyatul Aulad Nglanjuk Cepu Blora implanted through the hidden curriculum (Hidden Curriculum)? The purpose of this study is to analyze how character education instilled through the hidden curriculum in MI Tarbiyatul Aulad Nglanjuk Cepu Blora and conducting studies used in the foundation of what character education through the hidden curriculum in MI Tarbiyatul Aulad Nglanjuk Cepu Blora. Results of the study illustrate that character education in MI Tarbiyatul Aulad already running, mainly focused on the implementation of activities directly with practicing what has been taught in the school environment. Keywords: Education; Character; Hidden Curriculum